The Optimal Time of Ovarian Reserve Recovery After Laparoscopic Unilateral Ovarian Non-Endometriotic Cystectomy - Li, Huaping; Yan, Bin; Wang, Yanli; Shu, Zhiming; Li, Ping; Liu, Yahong; Wang, Ying; Ni, Xiaohong; Liu, Zhou (Frontiers in Endocrinology, 2021)
Background: Laparoscopic ovarian cystectomy is established as the standard surgical approach for the treatment of benign ovarian cyst. However, some previous studies have shown that potential fertility can be directly impaired by laparoscopic ovarian cystectomy, and diminished ovarian reserve (DOR), and even premature ovarian failure, respectively. Therefore, fertility-preserving interventions are required for benign gynecologic diseases. However, there is still little data on the time period required for recovery of ovarian reserve after the laparoscopic unilateral ovarian cystectomy, which is very important for the individualization of treatment protocols. This study aimed at investigating the time needed for the ovarian reserve to recover after laparoscopic unilateral ovarian nonendometriotic cystectomy. Materials and Methods: Sixty-seven patients with unilateral ovarian nonendometriotic cyst from Zhoupu and Punan Hospital who underwent laparoscopic unilateral ovarian cystectomy were recruited as a postoperative observation group (POG). Also, 69 healthy age-matched women without ovarian cyst who did not undergo surgery were recruited as a referent group (RFG). Ovarian reserve with the serum anti-Müllerian hormone (AMH), the follicle-stimulating hormone (FSH), estradiol (E2) levels, ovarian arterial resistance index (OARI), and antral follicle counts (AFC) was measured on the 3rd-5th day of the same menstrual cycle. A postoperative 6-month follow-up of cases was performed. Results: Compared with RFG, AFC of cyst side in POG group showed no difference in the 1st, 3rd, 6th postoperative month (F = 0.03, 0.02, 0.55; P = 0.873, 0.878, 0.460). The OARI of cyst side in POG group revealed no differences in the 1st, 3rd, 6th postoperative month (F = 0.73, 3.57, 1.75; P=0.395, 0.061, 0.701). In the first month, the postoperative AMH levels significantly declined reaching 1.88 ng/ml (IQR: 1.61-2.16 ng/ml) in POG and 2.57 ng/ml (IQR: 2.32-2.83 ng/ml) in RFG (F = 13.43; P = 0.000). At this same time interval, the postoperative rate of decline was significantly lower compared to the preoperative one in POG (32.75 %). The same trend was observed between POG and RFG group (26.67 %). Conclusions: The optimal time for recovery of ovarian reserve after the laparoscopic unilateral ovarian cystectomy is estimated to be six months.